Design and Implementation of Taizhou Integrated Prostate Screening. Issue 6 (November 2022) - Li, Fei-Ping; Zhang, Mei-Xian; Wang, Li-Jun; Zhu, Xiao-Liang; Sun, Liang-Xue; Chen, Zhi-Xia; Chen, Wei-Ying; Liu, Ding-Yi; Li, Hai-Ping; Jiang, Yu-Ying; Tung, Tao-Hsin
A community-based prostate cancer screening program was conducted to assess the morbidity and associated factors for prostate cancer among the subpopulation of men aged ≥50 years in Taizhou, China. Taizhou Integrated Prostate Screening (TIPS) is a large, observational, population-based study of prostate cancer screening data based on serum prostate-specific antigen (PSA) concentrations. A pilot census of all male residents aged 50 years or older was conducted in Luqiao District, one of the field sites of the TIPS cohort in the city of Taizhou, Zhejiang. The interviewer-administered questionnaire evaluated demographic characteristics and environmental exposure factors. A total of 1, 806 out of 3, 516 participants completed the questionnaire. The overall prevalence of PSA ≥4 ng/mL was 11.5%, and included participants at low risk (9.2%), moderate risk (1.7%), and high risk (0.6%). Participants aged 60–69, 70–79, and ≥80 years had a 2.7-fold, 4.2-fold, and 6.5-fold higher risk of elevated PSA, respectively, in comparison with those aged 50 to 59 years ( p < .001). Eighteen patients were diagnosed with prostate cancer, of whom 11 (61.1%) underwent radical surgery. This community-based PSA screening program indicated the results for early detection of prostate cancer among men aged ≥50 years. Early screening and appropriate clinical therapy for the management of prostate cancer are essential in this subpopulation.